Web-Based Bereavement Care: A Systematic Review and Meta-Analysis - Wagner, Birgit; Rosenberg, Nicole; Hofmann, Laura; Maass, Ulrike (Frontiers in Psychiatry, 2020)
Background: Web-based interventions have been introduced as novel and effective treatments for mental disorders and, in recent years, specifically for the bereaved. However, a systematic summary of the effectiveness of online interventions for people experiencing bereavement is still missing. Objective: A systematic literature search was conducted by 4 reviewers who reviewed and meta-analytically summarized the evidence for web-based interventions for bereaved people. Methods: Systematic searches (PubMed, Web of Science, PsycInfo, PsycArticles, Medline, and CINAHL) resulted in seven randomized controlled trials (N = 1,257) that addressed adults having experienced bereavement using internet-based interventions. We used random effects models to summarize treatment effects for between-group comparisons (treatment vs. control at post), and stability over time (post vs. follow-up). Results: All web-based interventions were based on CBT. In comparison with control groups, the interventions showed moderate (g = .53) to large effects (g = .86) for symptoms of grief and PTSD, respectively. The effect for depression was small (g = .44). All effects were stable over time. A higher number of treatment sessions achieved higher effects for grief symptoms and more individual feedback increased effects for depression. Other moderators (i.e. dropout rate, time since loss, exposure) did not significantly reduce moderate degrees of heterogeneity between the studies. Limitations: The number of includable studies was low in this review resulting to lower power for moderator analyses in particular. Conclusions: Overall, the results of web-based bereavement interventions are promising, and its low-threshold approach might reduce barriers to bereavement care. Nonetheless, future research should further examine potential moderators and specific treatment components (e.g. exposure, feedback) and compare interventions with active controls.